CaPOW! Using Problem Sets in a Capstone Course to Improve Fourth-Year Medical Students' Confidence in Self-Directed Learning. (March 2017) - Clay, Alison S.; Ming, David Y.; Knudsen, Nancy W.; Engle, Deborah L.; Grochowski, Colleen O'Connor; Andolsek, Kathryn M.; Chudgar, Saumil M.
Abstract : Problem: Despite the importance of self-directed learning (SDL) in the field of medicine, individuals are rarely taught how to perform SDL or receive feedback on it. Trainee skill in SDL is limited by difficulties with self-assessment and goal setting. Approach: Ninety-two graduating fourth-year medical students from Duke University School of Medicine completed an individualized learning plan (ILP) for a transition-to-residency Capstone course in spring 2015 to help foster their skills in SDL. Students completed the ILP after receiving a personalized report from a designated faculty coach detailing strengths and weaknesses on specific topics (e.g., pulmonary medicine) and clinical skills (e.g., generating a differential diagnosis). These were determined by their performance on 12 Capstone Problem Sets of the Week (CaPOWs) compared with their peers. Students used transitional-year milestones to self-assess their confidence in SDL. Outcomes: SDL was successfully implemented in a Capstone course through the development of required clinically oriented problem sets. Coaches provided guided feedback on students' performance to help them identify knowledge deficits. Students' self-assessment of their confidence in SDL increased following course completion. However, students often chose Capstone didactic sessions according to factors other than their CaPOW performance, including perceived relevance to planned specialty and session timing. Next Steps: Future Capstone curriculum changes may further enhance SDL skills of graduating students. Students will receive increased formative feedback on their CaPOW performance and be incentivized to attend sessions in areas of personal weakness.